2018
DOI: 10.1186/s40409-018-0158-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the cDNA encoding for SpCTx: a lethal factor from scorpionfish venom (Scorpaena plumieri)

Abstract: BackgroundLethal factors are multifunctional oligomeric proteins found in the venomous apparatus of Scorpaeniformes fish. These toxins elicit not only an array of biological responses in vitro but also cardiovascular disorders and strong hemolytic, nociceptive and edematogenic activities in vivo. This work describes the cloning and molecular identification of two toxin subunits, denominated Sp-CTx-α and Sp-CTx-β, from scorpionfish venom (Scorpaena plumieri).MethodsThe primary structures were deduced after cDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Female Aedes aegypti mosquitoes—vectors of the dengue ( Guzman and Harris, 2015 ), Zika ( Alfonso-Parra and Avila, 2018 ) and yellow fever viruses ( Chippaux and Chippaux, 2018 ), among others—display significantly reduced sexual receptivity shortly after mating ( Degner and Harrington, 2016a ). The reduction in sexual receptivity is mediated by SFPs produced in the accessory gland of the male reproductive tract ( Craig, 1967 ; Helinski et al, 2012a ).…”
Section: Introductionmentioning
confidence: 99%
“…Female Aedes aegypti mosquitoes—vectors of the dengue ( Guzman and Harris, 2015 ), Zika ( Alfonso-Parra and Avila, 2018 ) and yellow fever viruses ( Chippaux and Chippaux, 2018 ), among others—display significantly reduced sexual receptivity shortly after mating ( Degner and Harrington, 2016a ). The reduction in sexual receptivity is mediated by SFPs produced in the accessory gland of the male reproductive tract ( Craig, 1967 ; Helinski et al, 2012a ).…”
Section: Introductionmentioning
confidence: 99%
“…Because there are few fish toxin sequences available as references, most of them are from Scorpaenidae and Synanceiidae families, it is challenging to research fish toxins and to create quick and effective techniques for wide exploration of toxin proteins or genes (Xie et al, 2017). Some recent studies have isolated and provided several toxins sequences using different techniques (Smith and Wheeler, 2006;Xie et al, 2016;Costa et al, 2018;Xie et al, 2019;Campos et al, 2021;Lopes-Ferreira et al, 2022), but due to a given number of venomous fish (>2000 species) (Saggiomo et al, 2021), it would be just a small portion of it.…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 99%
“…However, this method takes a long time and uses a lot of crude venoms. Studies have shown, cDNA cloning and genomic sequencing were used to identify the full amino acids sequences of various toxins including SNTX (Chun, 2004), verrucotoxin (VTX) (Ziegman and Alewood, 2015), cytolysins (Campos et al, 2021), lectin (Nakagawa et al, 2015;Ziegman et al, 2019;Lopes-Ferreira et al, 2022), Sp-CTx (Costa et al, 2018), and hyaluronidases (Ziegman et al, 2019) and among the others in which most of them exhibit high sequence identity among and between species.…”
Section: Hypodytes Rubripinnis Nocitoxin 160kdamentioning
confidence: 99%
“…The complete amino acid sequences of several fish cytolysins were determined by cDNA cloning and/or genomic sequencing [13,14,39,40,45,[52][53][54] (Figure 2). Alignments were performed on Muscle server.…”
Section: Analyzing the Structural Features Of Fish Cytolysinsmentioning
confidence: 99%
“…The presence of the MACPF/CDC domain in fish cytolysins [53,55] and the inhibitory effect of cholesterol on the hemolytic activity of Sp-CTx [43] suggest that this lipid is also required for the interaction between these toxins and the erythrocyte membrane, much like the MACPF/CDC proteins found in bacteria.…”
Section: The Ubiquitous Hemolytic Activity Of Fish Cytolysins: From T...mentioning
confidence: 99%